Lipid Profile Status of Chronic Obstructive Pulmonary Disease in Hospitalized Patients (Bangladesh Journal of Medical Biochemistry, 2013)
The aim of this study was to evaluate the serum level of total cholesterol, triglycerides (TG), low density lipoproteins (LDL) and high density lipoproteins, (HDL) in chronic obstructive pulmonary disease (COPD) patients admitted in National Institute of Disease of Chest and Hospital, Mohakhali, Dhaka during. January 2009 to January 2010. Twenty two patients with COPD and 22 healthy controls were included in this study. Total cholesterol, HDL and TG levels were determined with ILAB 1800 Chemistry Analyzer using ILAB test Reagents. LDL concentration was calculated using the Friedewald Equation. The mean level of TG was 150.04±29.66 mg/dl and 126.14±13.28 in COPD patients and healthy control, respectively. A statistically significant difference was found between the two groups (p